2015
DOI: 10.1136/bmj.h217
|View full text |Cite
|
Sign up to set email alerts
|

Labour induction with prostaglandins: a systematic review and network meta-analysis

Abstract: ObjeCtives To assess the effectiveness and safety of prostaglandins used for labour induction. Design Systematic review with Bayesian network metaanalysis Data sOurCesThe Cochrane Pregnancy and Childbirth Group's Database of Trials (which incorporates the results of a broad generic search for all pregnancy and postpartum trials). Sources included are CENTRAL, Medline, Embase, NHS Economic Evaluation Database, CINAHL, relevant journals, conference proceedings, and registries of ongoing trials.eligibility Criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
111
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 27 publications
5
111
1
5
Order By: Relevance
“…4,5 Most research regarding induction of labor has focused on methods and different management strategies, with little attention for women's experiences and preferences. 6,7 In a prospective cohort study among 936 women, those who had their labor induced had a less positive birth experience compared with spontaneous labor (odds ratio [OR]: 1.5; 95% confidence interval [CI]: 1.0-2.3). 5 Also, women who had their labor induced were less satisfied with the care received compared with women who had spontaneous onset of labor.…”
mentioning
confidence: 99%
“…4,5 Most research regarding induction of labor has focused on methods and different management strategies, with little attention for women's experiences and preferences. 6,7 In a prospective cohort study among 936 women, those who had their labor induced had a less positive birth experience compared with spontaneous labor (odds ratio [OR]: 1.5; 95% confidence interval [CI]: 1.0-2.3). 5 Also, women who had their labor induced were less satisfied with the care received compared with women who had spontaneous onset of labor.…”
mentioning
confidence: 99%
“…All studies have concluded that it is an effective medication for this indication [10][11][12]. WHO recommends that cervical ripening with misoprostol should have a maximum duration of 24 h [31].…”
Section: Discussionmentioning
confidence: 99%
“…The oral route may result in improved clinical outcomes over the vaginal route [10,11], and women's convenience and comfort also seem to be increased [15][16][17][18]. The regimens most frequently used were either 20-25 mg every 2 h for a maximum of 12 doses (24 h), or 50 mg every 4 h for a maximum of 6 doses (24 h).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently completed UK National Institute of Health Research (NIHR) funded network and cost‐effectiveness analysis included 31 induction regimes evaluated in 611 trials with over 100 000 trial participants. Titrated low‐dose oral misoprostol was identified as likely to be the most cost‐effective method, and also had a favourable safety profile 5, 6. Sublingual or buccal misoprostol had significantly higher rates of hyperstimulation.…”
mentioning
confidence: 99%